A beam steering patch array antenna for wimax application - Jusoh, M. (2013)
A patch antenna design for switchable beam steer ability is proposed in this research. The presented antenna has successfully achieved beam steer functionality at four angle directions of +179°, -14°, +3° and 14°. The novel design of spiral feed network and differences of radiating element sizes have eventually helped to steer the main lobe radiation. Moreover, the switchable antenna is achieved by certain PIN diode configuration that positioned at the specific location of the antenna aperture feed. The proposed antenna realized a compact substrate dimension of 100 mm × 100 mm. All designs and simulations have been carried out using CST Microwave Studio. This antenna is potentially useful for Wireless Interoperability Microwave Access (WiMAX) smart antenna system.